Integration of TQM practices and ERP to enhance innovation culture and innovative work behavior: A proposed framework - Ahmad, Abdulla Obaid; Fam, Soo-Fen; Chuan, Zun Liang; Wahjono, Sentot Imam; Mohd Nusa, Najwa; Husseini, Saleh Ali (ASR Research India, 2022)
One of the most important technological innovations of the last decade has been the emergence of ERP solutions. But implementation of ERP is not just a technological challenge. It's a socio-technological endeavor, which mandates modifying existing applications and redesigning critical business processes to facilitate ERP implementation. Hence, there are organizational and cultural issues, which determine the success of ERP implementation. The main objective of implementing an ERP system is to integrate the organizations business processes and operations for improved business results. But not all organizations have been successful in the ERP implementation. The aim of this paper is an attempt to integrate the concept of TQM practices with ERP to enhance innovative work behavior as a part of corporate strategy in an organization. The results confirmed the positive and significant effects of TQM practices and ERP to enhance innovative work behavior. The mediation role of innovation culture between TQM practices and ERP and innovative work behavior also was confirmed. Throughout this study, further details and valuable implications have been discussed. Findings also help practitioners and managers make proper decisions when implementing TQM, ERP, and excellence practices in their organizations. With the joint effect of TQM practices, ERP and innovative work behavior, organizations can achieve maximum strong excellence and remain in a competitive market.